Quality of Pineapple Cobs Candy as The Effect of Citric Acid Concentration and Immersion Time - Achmad Rendika Putra; Lukman Hudi (jurnal makanan tropis dan teknologi agroindustri, 2021)
This study aims to determine the effect of citric acid concentration and immersion time on the characteristics of pineapple cobs candy using factorial randomized block design. The first factor was the concentration of citric acid (P): 0.2% (P1), 0.35% (P2), and 0.5% (P3), the second factor was immersion times (T): 12 hours (T1), 15 hours (T2) and 18 hours (T3). Statistical analysis used was analysis of variance and Tukey’s Honest Significant Difference at 5% level. Results showed that there was significant interaction between the concentration of citric acid and immersion times on the ash content of pineapple cobs candy. Concentration citric acid had significant effect on vitamin C content and lightness. Immersion times had significant effect on moisture content. Citric acid concentration and immersion times has significant affected on hedonic test of color, texture and taste. The best treatment was P2T1 (citric acid concentration 0.35%, immersion times 12 hours) with the characteristics ash content of 0.641%, water content of 10.966%, vitamin C content of 0.469%, lightness of 48.957, and color organoleptic value of 4.200, aroma of 5,433, texture of 5,100 and taste of 5,467.